Study on Ground-Test Simulation Method of the Ram Air for Commercial Airliners' Environmental Control System. (2015) - Ma, Zhe; Zhang, Xingjuan; Wang, Chao; Yang, Han; Yang, Chunxin
Abstract: Based on the equivalent heat transfer capacity, a closed simulation ground-test method of the ram air is proposed, it can provide the ram air's test condition for deriving the performance of commercial airliners' aircraft environmental control system (ECS). Analyzed results show that the proposed method can simulate different temperatures and pressures at the range of 0∼10 km flight altitudes under the compressor pressure ratio of 1.2 and turbine expansion ratio of 5. Temperatures and pressures can vary from -17.6 ∼ 40°C and 40∼101 kPa, respectively. In the meantime, compared to the traditional fan's simulation method, the energy consumption is decreased about 35%. By analyzing the key factors in method, it shows that altitudes and ACM characteristics can influence the power consumption and other conformance. Therefore, it needs to select ACM machine according to test requirements in engineering applications.